What is the value of e-procurement for suppliers? The drivers, barriers and opportunities for engaging MRO suppliers. (2nd April 2020) - Cardoso, Andre Luis; Biazzin, Cristiane
While an increasing number of studies recognise the importance of e-procurement tools (EPT), purchasing executives seem to face continuous challenges to engage suppliers to adopt such tools. This study aims to explore the barriers to maintenance, repair and operations (MRO) suppliers in adopting EPT, and how to overcome them by developing a multiple case study. Our findings indicate that suppliers' willingness to adopt EPT depends on the maintenance of ties and relations previously established with customers. While access to new customers is perceived as a driver to adopt EPT, its use demands robust investment in data management and technology, otherwise suppliers will increase their operational activities and costs. Moreover, suppliers who have the capability to integrate EPT into an intelligent system have a higher willingness to accept it.